Generation of student interest in an inquiry-based mobile learning environment - Laine, Erkka; Veermans, Marjaana; Lahti, Aleksi; Veermans, Koen (Frontline Learning Research, 2017)
A declining trend in adolescents’ interest in science learning and attitudes towards science-related careers has been reported during recent years. There has been a call for more motivating learning environments that inspire students to develop interest towards science. This study examines students’ interest development in STEM subjects in an ecologically valid setting during one school year and how features of the learning environment affect students’ generation of interest. In a quasi-experimental study design, one class of 7th grade (aged 12 to 13 years) students (N = 18) studied in an inquiry-based mobile learning environment that had a special emphasis on integrated curriculum. Interest variables were measured three times and focus group interviews were held twice during the school year. From a group of 113 students studying in an ordinary learning setting, a propensity score-matched control group of 18 students was selected based on general self-efficacy, intrinsic goal orientation, interest in technology, and web-user self-efficacy. Results from the quantitative analyses revealed only minor differences between the two groups. Results from the qualitative analyses indicate that students found the new environment to be interest generating, thus ascribing to the general idea and aim of the new environment, but also that the implementation was in many cases far from ideal, indicating that much of its potential was unrealized.